Nurses and Night Shifts: Poor Sleep Quality Exacerbates Psychomotor Performance - Di Muzio, Marco; Diella, Giulia; Di Simone, Emanuele; Novelli, Luana; Alfonsi, Valentina; Scarpelli, Serena; Annarumma, Ludovica; Salfi, Federico; Pazzaglia, Mariella; Giannini, Anna Maria; De Gennaro, Luigi (Frontiers in Neuroscience, 2020)
In Europe, 40% of healthcare employees are involved in shift work. The altered sleep/wake rhythm of night shift nurses is also associated with deteriorated cognitive efficiency. In this study, we examine the effects of the night shift on psychomotor performance, sleepiness and tiredness in a large sample of shift-working nurses, and evaluated if poor sleep quality, sex, age, or years on the job could impact on a better adaptation to shift work. Eighty-six nurses with 8-hours-rapidly-rotating-shifts were evaluated at the end of three shifts (Morning/Afternoon/Night), for sleepiness and tiredness. Sleepiness, as measured by the Karolinska Sleepiness Scale, and tiredness, as measured by the Tiredness Symptoms Scale, were more pronounced after the night shift. These increases were paralleled by lower attentional performance on the Psychomotor Vigilance Task (PVT) after the night shift. While sex, age, and years on the job did not affect PVT performance after the night shift, lower sleep quality (Pittsburgh Sleep Quality, PSQI>5) was associated with decreased performance. The high prevalence of altered sleep quality showed that nurses, and shift workers in general, are at risk for a poor sleep quality.. The evaluation of sleep quality through PSQI could represent a rapid, inexpensive tool to assess healthcare workers assigned to rotating night shifts or to evaluate nurses who coped poorly with night shift work.